Sequencing analysis of partial n gene of feline morbillivirus from Malaysia - Makhtar, Siti Tasnim; Tan, Sheau Wei; Omar, Abdul Rahman; Mustaffa-Kamal, Farina (Universiti Putra Malaysia, 2022)
Feline morbillivirus (FeMV) is a new emerging virus of domestic cats categorized under the genus of (Morbillivirus, associated with chronic kidney disease (CKD). The origin of the virus is yet to be determined, and whether it is caused by a spill-over event from wildlife or domestic cats remains speculative. Recombination event has been reported in FeMV isolate found in Japan; therefore, characterization of FeMV strains isolated in Malaysia (i.e., FeMV-Malaysia isolates) may provide some insight, thus adding some information on the viral evolution of FeMV. Therefore, this study aims to conduct a phylogenetic analysis and assess any genetic changes in the N gene of FeMV-Malaysia isolates. Through sequencing of N gene of seven isolates using three overlapping primer sets, the sequences spanning approximately 1.5kb of FeMV-N gene were obtained. DNA sequencing, nucleotide sequences, amino acid residues alignments, and phylogenetic analysis were performed. A nucleotide sequence alignment was also performed to compare the isolates obtained from two previous studies. From the alignment mentioned above, there were 19 variable sites of which there were absence of amino acid changes except for isolate UPM210 at position 806 and isolate UPM315 at position 823. Furthermore, protein alignment was done to compare FeMV-Malaysia isolates with FeMV strains from other countries, along with other morbillivirus-related isolates. From one of the conserved regions located within the N gene, similar amino acid sequences were detected across different morbilliviruses. Lastly, from the phylogenetic tree, it was illustrated that all partial FeMV-N gene Malaysia isolates sequenced in this study were clustered together in the same clade whereby these FeMV-N genes Malaysia isolates shared a common ancestor with isolates from Japan (SS3, MiJP003, ChJP073) and Thailand (Thai-U16, CTL16. CTL43).